Antibacterial Activity and Interaction of Ethanolic Extracts of Bidens pilosa L. Leaves and Ginger Rhizomes against the Growth of Escherichia coli in Vitro - Seran, Lukas; Herak, Rikardus (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
This study aimed to analyze the antibacterial activity of ethanolic extracts of bidens pilosa L. leaves and ginger rhizomes, both individually and in combination, and to evaluate their interaction against the growth of Escherichia coli in vitro. This study was a laboratory experiment employing a posttest-only control group design. The extracts were obtained through ethanol maceration. Antibacterial activity was tested using the agar well diffusion method to measure inhibition zone diameter, the dilution method to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC), and the checkerboard assay to assess extract interaction through the Fractional Inhibitory Concentration Index (FICI). The ethanolic extracts of bidens pilosa L. leaves and ginger rhizomes exhibited antibacterial activity against E. coli, with stronger inhibition observed at higher concentrations. The extraction yields of ketul leaves and ginger rhizomes were 9.4% and 12.8%, respectively. The MIC values of ketul leaf and ginger rhizome extracts were 25 mg/mL and 12.5 mg/mL, respectively, while their combination decreased to 6.25 mg/mL. The combined extracts also produced larger inhibition zones than the single extracts. A FICI value of 0.75 indicated an additive interaction. The combination of ethanolic extracts of bidens pilosa L. leaves and ginger rhizomes has potential as a natural antibacterial agent against Escherichia coli. Aktivitas Antibakteri dan Interaksi Ekstrak Etanol Daun Bidens pilosa L. dan Rimpang Jahe terhadap Pertumbuhan Escherichia coli secara In Vitro ABSTRAK: Penelitian ini bertujuan menganalisis aktivitas antibakteri ekstrak etanol daun bidens pilosa L. dan rimpang jahe, baik secara tunggal maupun kombinasi, serta menilai interaksinya terhadap pertumbuhan Escherichia coli secara in vitro. Penelitian ini merupakan eksperimen laboratorium dengan rancangan posttest-only control group design. Ekstrak diperoleh melalui maserasi menggunakan etanol. Uji antibakteri dilakukan dengan metode difusi sumuran untuk mengukur diameter zona hambat, metode dilusi untuk menentukan Minimum Inhibitory Concentration (MIC) dan Minimum Bactericidal Concentration (MBC), serta checkerboard assay untuk menilai interaksi kombinasi ekstrak melalui Fractional Inhibitory Concentration Index (FICI). Ekstrak etanol daun bidens pilosa L. dan rimpang jahe menunjukkan aktivitas antibakteri terhadap E. coli, dengan daya hambat yang meningkat seiring peningkatan konsentrasi. Rendemen ekstrak daun ketul dan jahe masing-masing sebesar 9,4% dan 12,8%. Nilai MIC ekstrak daun ketul dan jahe berturut-turut sebesar 25 mg/mL dan 12,5 mg/mL, sedangkan kombinasi keduanya menurun menjadi 6,25 mg/ml. Kombinasi ekstrak juga menghasilkan zona hambat lebih besar dibandingkan ekstrak tunggal. Nilai FICI sebesar 0,75 menunjukkan interaksi aditif. Kesimpulan singkat: Kombinasi ekstrak etanol daun bidens pilosa L. dan rimpang jahe berpotensi dikembangkan sebagai agen antibakterii terhadap Escherichia coli.